Substantiation of parametres of springs vibro tines - L. F. Babitsky; I. V. Sobolevsky; V. A. Kuklin (Аграрная наука Евро-Северо-Востока)
The most energy-intensive operation in cultivation of agricultural crops is a soil treatment, which spent up to 40% energy. Among the system of measures to reduce the energy intensity of tillers most important is the use of vibration of working bodies. Vibration of working bodies can be carried out using a forced drive. However, the energy costs of a forced drive to work sometimes exceed the energy costs of passive working bodies. Therefore, it is more appropriate to imparting elastic vibration tillage working bodies due to variable soil resistance in accordance with the phases of deformation and destruction of the soil. The most effective is a vibro-impact effects of the working body on the ground with the use of vibro-impact self-adjusting mechanisms. The object of theoretical study is selected construction of cultivators' paws on the resilient C-shaped stand, the upper part of which is designed as a helical coil spring with hemispherical strikers. When making parameters of vibro spring force action it was considered in view of the current soil resistance. In justifying the design parameters and operating conditions it were used theoretical methods and agricultural mechanics, continuum mechanics, elasticity theory, integral and differential calculus. Given the known forces of resistance to movement through the soil of cultivators paws with vibro-impact spring and sediment spring, taking into account the radius of hemispheric drummers on coils of vibro-impact springs theoretical dependences for definition of key parameters of vibro-impact springs were obtained: wire radius, the radius of the vibro-impact spring, and the number of its active coils. Taking into account the maximum permissible load vibro-impact spring should be used for the manufacture of spring wire. Vibro-impact spring will contribute to self-oscillation.